Improving The Integration and Connectivity of Feeder Wira Wiri, Suroboyo Bus, Trans Semanggi Bus, and Trans Jatim Bus in Surabaya City Purabaya-Rajawali Routes - Khairunnisa, Shaafiyah Zahroo; Widyastuti, Hera (Institut Teknologi Sepuluh Nopember, 2024)
Surabaya City has several public transportation such as Feeder Wira Wiri and Suroboyo Bus managed by Surabaya City Government, Bus Trans Semanggi managed by the Ministry of Transportation of the Republic of Indonesia, and Bus Trans Jatim managed by East Java Provincial Government. Based on observations in Purabaya-Rajawali routes, these public transportation services have yet to achieve maximum integration between modes, hence requiring analysis to improve the integration and connectivity of these public transportation systems. This analysis assesses customer satisfaction regarding the integration and connectivity of Feeder Wira Wiri, Suroboyo Bus, Trans Semanggi Bus, and Trans Jatim Bus along the Purabaya-Rajawali routes in Surabaya City. The methods used Customer Satisfaction Index (CSI) to calculate user level of user satisfaction and Quality Function Deployment (QFD) used by integrating Importance-Perfomance Analysis (IPA) and Kano model. From the analysis results, the satisfaction level indicates a value of 68.01% (satisfied). So, it is needed to improve existing attribute integration. From this analysis, 11 technical responses were obtained to improve integration attributes. The final result of this research indicates that 11 improvements of integration attributes can be implemented in the integration system between services of Feeder Wira Wiri, Suroboyo Bus, Trans Semanggi Bus, and Trans Jatim Bus in Surabaya City Purabaya-Rajawali routes.